USING GROUP WORK STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION SKILL - Adib Ahmada (UIBU, 2020)
The reading comprehension skill of the First Semester class of English Education Department of Islamic Institute of Darussalam Blokagung Banyuwangi in Academic Year 2018/2019 was low. It could be seen based on the result of preliminary study that was conducted by the researcher. Therefore, the researcher tried to use group work strategy to solve the problems. Since the study aimed to improve the students’ reading comprehension skill, the researcher used a Classroom Action Research as a research design. This research was conducted at the First Semester class of English Education Department of Islamic Institute of Darussalam Blokagung Banyuwangi that consists of 25 students. To measure their improvement in reading comprehension, the lecturer had determined the criteria of success. It was if the students reached the score above 70. The researcher found that group work strategy could improve students’ reading skill. The students reading skill increased from 24%, 64%, to 92% (preliminary study, the first cycle and the second cycle).